Comparative assessment of phenolic compounds and antioxidant properties of green tea made by microwave assisted and stove heating - Javad, Sumera; Ahmad, Asma; Akhtar, Iqra; Ghaffar, Nadia; Jabeen, Khajista (Bangladesh Journal of Botany, 2020)
Efficiency of microwave-assisted extraction (MAE) and a commonly practiced brewing method, i.e. heating on stove were compared for preparation of green tea (Camellia sinensis L.). The steeping time was invariant as 2 min. Three green tea samples (Lipton, Tapal and local herbal green tea) were used in the present experiment. Results showed that microwave extracts had significantly higher quantities of phenolics and flavonoids from all tea samples as compared to conventional stove heating. Moreover, microwave assisted extraction showed highest amount (2.19%) of gallic acid in Lipton green tea while the Quercetin content (1.23%) was found invariable in the samples.